Precisely NIR-II-activated and pH-responsive cascade catalytic nanoreactor for controlled drug release and self-enhanced synergetic therapy. Issue 34 (18th May 2022) - Hu, Peng; Zhao, Shuang; Shi, Jiahua; Li, Fan; Wang, Shaochen; Gan, Ying; Liu, Lei; Yu, Shuling
Abstract : Efficient NIR-II laser and pH-responsive cascade catalytic nanoplatform (HMPDA@Cu2− x Se-DOX-GOx@PCM) for controlled drug release and self-enhanced synergetic therapy. Abstract : Mesoporous polydopamine (MPDA) and MPDA-based nanosystems have been widely used in the field of photothermal therapy (PTT) and drug delivery. However, synthesis of the corresponding nanoplatforms for efficient PTT and controlled drug release simultaneously in the second near infrared (NIR-II) region remains a great challenge. Herein, a NIR-II and pH dual-responsive HMPDA@Cu2− x Se cascade catalytic nanoplatform was constructed by assembling hollow mesoporous polydopamine (HMPDA) with ultra-small Cu2− x Se, which could compensate the inadequate NIR-II-induced PTT effect of HMPDA and enhance the efficacy of chemodynamic therapy (CDT) simultaneously under NIR-II laser irradiation. Meanwhile, doxorubicin (DOX) and glucose oxidase (GOx) were encapsulated into the synthesized HMPDA@Cu2− x Se using the photothermal-induced phase change material (PCM) tetradecyl (1-TD) as a gatekeeper to achieve the controlled release of the cargo. Under 1064 nm laser, the generated heat could cause 1-TD melting, resulting in the release of large amounts of DOX and GOx. The released GOx could further catalyze glucose to H2 O2 and gluconic acid, which in turn promoted the effects of PTT/CDT and the release of drugs. In vitro and in vivo experiments showed that the synthesized HMPDA@Cu2− x Se-DOX-GOx@PCM (HMPC-D/G@PCM) nanosystem exhibited a significant tumor cell inhibition effect by combining different treatment modes. Thus, this smart nanoplatform with multiple stimuli-activated cascade reactions provided a new idea for designing effective multi-modal combination therapy for tumors.